A) Przekształć iloczyny na sumy:
a. (x + √2) * (2√2 + x)=
b.(2x²√5 - 2) * (x√5-√5)=
B) Wykonaj mnożenie i zredaguj wyrazy podobne.
c.(x-1)*(x³+x²+x+1)=
d.(x+1)(x³-x²+x-1)=
C) Zapisz w jak najprostszej postaci:
e)(5k+n)*(k-2n)-k*(4k+n)=
f)(4p-3r)*(p+2r)-(3p-r)(p+6r)=

1

Odpowiedzi

Najlepsza Odpowiedź!
2009-11-17T16:59:31+01:00
1.
(x+√2)*(2√2+x)=2√2x+x²+4+√2x
(2x²√5-2)*(x√5-√5)=10x³-10x²-2x√5-2√5
2
c)=x⁴+x³+x²+x-x³-x²-x-1=x⁴-1
d)=x⁴-x³+x²-x+x³-x²+x-1=x⁴-1
3
e)=5k²-10kn+kn-2n²-4k²-kn=k²-2n²-10kn
f)=4p²+8pr-3pr-6r²-(3p²+18pr-pr-6r²)=4p²+5pr-6r²-3p²-18pr+pr+6r²=p²-12p